PERCOBAAN PEMBUATAN DEKSTRIN DARI TEPUNG SAGU (Metroxylon spp.) - Yacob Ando; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The experimental study of dextryn manufacture was conducted at the Forest Products Research and Development Centre laboratory in Bogor. The sago flour was obtained from Riau, originally extracted from female sago as signified by the absence of spine on the leaves. The sago starch was manufactured into dextryin at 80oC starting reaction temperature. Prior to the reaction sufficient amount of sago starch was bleached with 1% CaOCl2. The starch was allowed to settle down and dried. Umbleached sago starch was prepared as control. During the dextryn manufacture the HCl was gradually sprayed to the starch while elevating the temperature to 120oC, at which it was maintained for 2 hours. The reaction products were then tested and the properties compared with that of the existing standard. The quality of the dextryn manufactured was evaluated and discussed. The result of the experiment was slighty inverior compared with that of the superior and prima quality due to the low dextryn content.